Clarence Day's "Life with father" - Curtiz, Michael, 1888-1962; Powell, William, 1892-1984; Dunne, Irene, 1898-1990; Lindsay, Howard, 1889-1968.; Day, Clarence, 1874-1935.; Warner Bros. Pictures (1923-1967); Cinetel Films ([Burbank, CA] : Warner Bros., 1947)
In late nineteenth century New York a Wall Street broker likes to think his house runs his way, but finds himself constantly bemused at how much of what happens is down to his wife. His children are also stretching their wings, discovering girls and making money out of patent medicine selling. When it comes to light he has never been baptized and everyone starts insisting he must do so, it all starts to get a bit too much. --
"From the original play by Howard Lindsay and Russel Crouse, from Oscar Serlin's stage production."
William Powell, Irene Dunne, Elizabeth Taylor, Edmund Gwenn, ZaSu Pitts, Jimmy Lydon, Moroni Olsen.
Directors of photography, Peverell Marley, William V. Skall; editor, George Amy; music, Max Steiner.
In English or Spanish.
Winner of 1 Golden Globe in 1948: Best Score, Motion Picture
Winner of 1 NYFCC Award in 1947: Best Actor (William Powell)
Keywords: Families -- New York (State) -- New York -- Drama; Fathers -- Drama; Baptism -- Drama; Comedy films; Domestic comedy films; Film adaptations; Internet videos; Streaming video